2008
DOI: 10.1080/07357900701708385
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Instability in Patients with Non-Small Cell Lung Cancer Assessed by the Arbitrarily Primed Polymerase Chain Reaction

Abstract: In the present study, we used DNA profiling to measure genomic instability in 22 patients with non-small cell lung cancer (NSCLC). Genomic instability was correlated with gender, the age of the patients at the time of diagnosis, the NSCLC subtype, histological grade and stage of the tumor, necrosis presence in the tumor and lymph node invasion. Genomic instability was significantly higher in patients older than 50 and those with adenocarcinoma compared to squamous-cell carcinoma. Most importantly, genomic inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The needle was dipped in the PCR master mix for 2 min and then discarded. The PCR products were reamplified with the same primers used for AP-PCR reactions at high-stringency conditions specific for each particular primer [5]. The reamplified material was administrated on 1.5% agarose gels, purified using DNA Extraction Kit (Fermentas Life Sciences, Lithuania) and cloned with GeneJet TM PCR Cloning Kit (Fermentas Life Sciences, Lithuania) according to manufacturers' instructions.…”
Section: Isolation Cloning and Sequencing Of Variant Electrophoreticmentioning
confidence: 99%
See 2 more Smart Citations
“…The needle was dipped in the PCR master mix for 2 min and then discarded. The PCR products were reamplified with the same primers used for AP-PCR reactions at high-stringency conditions specific for each particular primer [5]. The reamplified material was administrated on 1.5% agarose gels, purified using DNA Extraction Kit (Fermentas Life Sciences, Lithuania) and cloned with GeneJet TM PCR Cloning Kit (Fermentas Life Sciences, Lithuania) according to manufacturers' instructions.…”
Section: Isolation Cloning and Sequencing Of Variant Electrophoreticmentioning
confidence: 99%
“…Five primers (p53 A, MDR A, E5A p53, GAPDH A, and GAPDH S) produced informative sequence alterations differentiating normal tissue from tumor tissue. Primer sequences (p53 A, MDR A, E5A p53 and GAPDH A), AP-PCR conditions and reaction mixtures are as described previously [5] including one additional primer GAPDHS: 5 -CGG AGT CAA CGG ATT TGG TCG TAT -3 ; AP-PCR low-stringency conditions: 95 • C 30 ; 50 • C 2 ; 72 • C 1 ; AP-PCR high-stringency conditions: 95 • C 30 ; 70 • C 1 ; 72 • C 1 and AP-PCR reaction mixture: 0.4 mM each dNTP; 2.5 mM MgCl 2 ; 5 M of a primer; 1 U of Taq DNA polymerase.…”
Section: Ap-pcr Dna Fingerprintingmentioning
confidence: 99%
See 1 more Smart Citation
“…The high incidence of genomic instability in lung cancers is wellestablished and in some cases it has been associated with poor prognosis (1)(2)(3). To guarantee genomic stability under the conditions of continuous genotoxic stress, a coordinated DNA damage surveillance system and several DNA repair pathways have been evolutionally developed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted on the lung cancer have shown frequent genomic imbalances (Markovic et al, 2008), and it is suggested that chromosomal instability plays an important role in its progression (Ninomiya et al, 2006). Structural chromosomal rearrangements and losses/gains from non-disjunctions and multipolar mitoses are thought to result in aneuploidy.…”
Section: Discussionmentioning
confidence: 99%